Prevalence and risk factors for colonization by Clostridium difficile and extended-spectrum β-lactamase-producing Enterobacteriaceae in rehabilitation clinics in Germany. Issue 1 (January 2018) - Arvand, M.; Ruscher, C.; Bettge-Weller, G.; Goltz, M.; Pfeifer, Y.
Summary: Background: Rehabilitation clinics may vary widely in terms of type of care provided, duration of hospital stay, and case severity. Few data are available on prevalence of Clostridium difficile or extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL-E) colonization in rehabilitation clinics in Germany. Aim: This study investigated the frequency of intestinal colonization by these pathogens among patients in rehabilitation clinics of different specialization. Methods: In the scope of a point prevalence study, faecal samples and demographic and clinical data were collected in five rehabilitation clinics. Samples were screened for C. difficile and ESBL-E by culture. Isolates were characterized by polymerase chain reaction for C. difficile toxins A and B, for β-lactamase genes, and by molecular typing including pulsed-field gel electrophoresis and PCR-based ribotyping. Findings: Of 305 patients screened, 11.1% were colonized by toxigenic C. difficile and 7.5% by ESBL-E. Colonization rates differed markedly between facilities, ranging from 1.6% to 26.3% for C. difficile and from zero to 23.7% for ESBL-E. Prevalence of colonization by C. difficile and ESBL-E was higher in neurological rehabilitation clinics than in clinics with other specialties ( P < 0.001). Molecular typing revealed six patients from one neurological rehabilitation clinic harbouring a unique C. difficile strain (ribotype 017). CTX-M-15 was the most prevalent ESBL type. We detected several indistinguishable pairs of ESBL-E isolates within some facilities. Conclusion: Significant differences were found in the prevalence of C. difficile and ESBL-E between rehabilitation clinics. Facilities providing specialized medical care for critically ill patients had higher prevalence rates. These results may help to delineate the requirements for infection prevention and control in rehabilitation clinics.